Management of Inflammatory Root Resorption of Maxillary Central Incisors following Traumatic Avulsion - Seyed Mohsen Sadeghi; Samaneh Moradi; Samaneh Soltani (Case Reports in Dentistry)
Background. Avulsion is among the most severe types of dental trauma, which often occurs at young ages and can compromise the long-term prognosis of the traumatized tooth. Case Report. Herein, we report replantation of two avulsed teeth. Our patient was an 11-year-old boy with two avulsed maxillary central incisors due to a bicycle fall 2 months earlier. The patient was referred to us after rigid splinting of his teeth by a surgeon. Long-term calcium hydroxide (CH) therapy was performed for the patient, and after healing of periodontal ligament (PDL), apexification was performed for both teeth followed by root canal therapy. During the 2-year follow-up, both teeth were functional and had no radiographic or clinical evidence of resorption or ankylosis. Conclusion. The reported case highlights the favorably high tissue healing potential following severe dental trauma, given that appropriate treatment is performed. Correct endodontic management can guarantee the long-term prognosis of teeth following severe dental trauma.